Upper limits on the total cosmic-ray luminosity of individual sources - Anjos, R. C. (2014)
In this paper, upper limits on the total luminosity of ultra-high-energy cosmic-rays (UHECR) (E > 10^18 eV) are determined for five individual sources. The upper limit on the integral flux of GeV-TeV gamma-rays is used to extract the upper limit on the total UHECR luminosity of individual sources. The correlation between upper limit on the integral GeV-TeV gamma-ray flux and upper limit on the UHECR luminosity is established through the cascading process that takes place during propagation of the cosmic rays in the background radiation fields, as explained in reference [1]. Twenty-eight sources measured by FERMI-LAT, VERITAS and MAGIC observatories have been studied. The measured upper limit on the GeV-TeV gamma-ray flux is restrictive enough to allow the calculation of an upper limit on the total UHECR cosmic-ray luminosity of five sources. The upper limit on the UHECR cosmic-ray luminosity of these sources is shown for several assumptions on the emission mechanism. For all studied sources an upper limit on the ultra-high-energy proton luminosity is also set.